2022
DOI: 10.1111/jan.15523
|View full text |Cite
|
Sign up to set email alerts
|

Burnout in nursing: A vision of gender and “invisible” unrecorded care

Abstract: Aim To reflect on how characteristics inherent in the nursing profession might be related to burnout syndrome among the nursing collective. Background Most people are unaware of the tasks and responsibilities of the nursing profession, as well as the burnout rates suffered by nurses. The nursing profession is a feminized profession, and this feminization may lead to the assignment of gender stereotypes and roles traditionally attributed to women. Much of the care provided by nurses is unrecorded, “invisible” a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 69 publications
1
4
0
Order By: Relevance
“…The relationship between burnout and gender is complex, and statistical analyses, gender stereotypes, perception of women in their role in the workforce, and unrecorded 'invisible' care either in work or at home may explain this relationship. 31 This study found that younger age was a risk factor for higher personal burnout and aligns with many previous studies reporting similar results. 6,26 In a systematic review and meta-analysis of burnout in mental health professionals, O'Connor et al 16 reported that levels of burnout typically decrease with age, whereas a study of neurologists suggested that the relationship between age and burnout may be non-linear, with a tendency to increase up to 40 years of age and then decrease.…”
Section: Covid-19-related Factorssupporting
confidence: 92%
See 1 more Smart Citation
“…The relationship between burnout and gender is complex, and statistical analyses, gender stereotypes, perception of women in their role in the workforce, and unrecorded 'invisible' care either in work or at home may explain this relationship. 31 This study found that younger age was a risk factor for higher personal burnout and aligns with many previous studies reporting similar results. 6,26 In a systematic review and meta-analysis of burnout in mental health professionals, O'Connor et al 16 reported that levels of burnout typically decrease with age, whereas a study of neurologists suggested that the relationship between age and burnout may be non-linear, with a tendency to increase up to 40 years of age and then decrease.…”
Section: Covid-19-related Factorssupporting
confidence: 92%
“…The relationship between burnout and gender is complex, and statistical analyses, gender stereotypes, perception of women in their role in the workforce, and unrecorded ‘invisible’ care either in work or at home may explain this relationship. 31 …”
Section: Discussionmentioning
confidence: 99%
“…Holistic nursing values the health and wellbeing of all nurses and healthcare providers and considers these essential components in providing exemplary healthcare. The COVID-19 pandemic and sociopolitical tension have led to a growing crisis of exhaustion, depression, and insomnia among nurses; many feel overwhelmed and a sense of impoverishment in their ability to remain engaged in current care systems (Montañés Muro et al, 2022). In these conditions, a nurse's capacity to heal is limited and is often severely compromised.…”
Section: Holistic Nursing Research Priorities 2023–2026mentioning
confidence: 99%
“…Additionally, the pandemic has destabilized the nursing workforce, as two-thirds of hospitals report nurse vacancy rates of 7.5% or higher (AHA, 2021). Moreover, approximately 50% of nurses will leave or have considered leaving the nursing profession as an outcome of burnout (Dall’Ora et al, 2020; Montañés Muro et al, 2022), a frightening prospect contributing to a critical nursing shortage. This destabilization led to an urgent need to address nurses’ wellbeing and the work environment to facilitate the retention of nurses in the workplace (Rosa et al, 2019).…”
Section: Holistic Nursing Research Priorities 2023–2026mentioning
confidence: 99%
See 1 more Smart Citation